1998
DOI: 10.1093/jn/128.10.1600
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Deprivation of Murine 3T3 Cells by Use of Diethylenetrinitrilopentaacetate Impairs DNA Synthesis upon Stimulation with Insulin-Like Growth Factor-I (IGF-I)

Abstract: Growth failure in zinc-deficient animals is associated with decreased DNA synthesis; zinc deprivation of 3T3 cells, by use of diethylenetrinitrilopentaacetate (DTPA), impairs thymidine incorporation when the cells are stimulated with fetal bovine serum (FBS). The purpose of this study was to determine the step of cell cycle progression that is affected by zinc deprivation. Swiss murine 3T3 cells were cultured for 3 d in complete media and then for 2 d in low serum media. Cells were then placed in serum-free me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…In our cellfree zinc-binding assay, the source of zinc that was incorporated into the proteins during bacterial culture growth was obtained from yeast extract used in the LB media (0.2 mM 18 ). This is a much higher concentration of that found in the media used to grow COS-7 cells for guanine deaminase assays (5 µM from the fetal bovine serum 19,20 ). It is unknown the concentration range of cellular zinc that is needed for cypin's effect on dendrite branching.…”
Section: Discussionmentioning
confidence: 93%
“…In our cellfree zinc-binding assay, the source of zinc that was incorporated into the proteins during bacterial culture growth was obtained from yeast extract used in the LB media (0.2 mM 18 ). This is a much higher concentration of that found in the media used to grow COS-7 cells for guanine deaminase assays (5 µM from the fetal bovine serum 19,20 ). It is unknown the concentration range of cellular zinc that is needed for cypin's effect on dendrite branching.…”
Section: Discussionmentioning
confidence: 93%
“…The effect of Zn 2ϩ in enhancing cell proliferation is synergistic with intracellular Ca 2ϩ rise, indicating that their effects are mediated through a common pathway (26,27). Importantly, Zn 2ϩ affects cell proliferation rate prior to changes in its intracellular levels, suggesting that the extracellular Zn 2ϩ pool mediates signaling leading to epithelial repair (28).…”
mentioning
confidence: 99%
“…It has been reported that, when cells are cultured in media containing an extracellular chelator, such as EDTA or DTPA, growth factor-induced DNA synthesis is impaired [MacDonald et al, 1998;Lefebvre et al, 1999]. There are six zincfingers of the C 2 H 2 type in the structure of MTFDC.…”
Section: Discussionmentioning
confidence: 99%